STRATEGI PEMASARAN DURIAN SANGGARAN (Duriozibethinus M.) DI KECAMATAN MATESIH KABUPATEN KARANGANYAR DENGAN METODE COMPETITIVE PROFILE MATRIX (CPM) (Jurnal Social Economic of Agriculture, 2012)
This research aims to identify critical success factor of internal and external, to formulate strategies alternative and to determine priority of Durian Sanggaran marketing strategy in Matesih Sub-District Karanganyar District. Research’s basic method is analytical descriptive method. Determination of Matesih Sub-District as the location of the research decided by purposive (on purpose). The type of data used are the primary data and secondary data. Data analysis methods used (1) Competitive Profile Matrix (CPM) to identify critical success factors, (2) SWOT matrix to formulate an alternative marketing strategy Durian Sanggaran, and (3 ) QSPM to determine priorities Durian Sanggaran marketing strategy. The analysis showed that (1) The first ranking of local durian in Matesih Sub District based on the Competitive Profile Matrix analysis is Durian Sanggaran with a total score of 2.909 (2) The Alternative strategies can be applied in the marketing of Durian Sanggaran in Matesih Sub-District Karanganyar Regency are: modify the product, make improvements durian stall traders, and forge partnerships with governments and financial institutions. (3) Priority strategies that can be applied in the marketing of Durian Sanggaran in Matesih District Karanganyar Regency is improving the durian stall traders.